2020
DOI: 10.1080/26410397.2020.1731296
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infection knowledge and attitudes among Muslim women worldwide: a systematic review

Abstract: Extramarital sexual relations are forbidden in Islam, and sexual health information is not readily available in Islamic communities, especially for women. This review aimed to explore sexually transmitted infection (STI) knowledge and attitudes among Muslim women worldwide. A systematic review was conducted on seven electronic databases. We included qualitative and quantitative studies of female Muslim participants of reproductive age, focusing on STI knowledge and attitudes. A narrative synthesis approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
4
27
2
Order By: Relevance
“…Shariati et al, , 2014bYari et al, 2015). Women and girls may experience opposition from family members when attempting to seek answers on sexual and reproductive health topics, mainly because sexual and reproductive health information and discussions are perceived as encouraging promiscuity and premarital sex (Kirby et al, 2007;Alomair et al, 2020aAlomair et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shariati et al, , 2014bYari et al, 2015). Women and girls may experience opposition from family members when attempting to seek answers on sexual and reproductive health topics, mainly because sexual and reproductive health information and discussions are perceived as encouraging promiscuity and premarital sex (Kirby et al, 2007;Alomair et al, 2020aAlomair et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that many women avoided sexual health information in order to maintain their image as sexually inexperienced, thus deemed of a good marriageable quality (Rahman, 2018). Sexual and reproductive health education for unmarried women is believed to be against Islamic religious beliefs since religious practices provide protection against sexually transmitted infections (Alomair et al, 2020a(Alomair et al, , 2020b. However, religious leaders have supporting views towards sexual and reproductive health education, with emphasis on tailored and religiously sensitive educational content (Mohammed Shariati et al, 2014a, 2014b.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first in-depth study of women's experiences and perceptions of SRH in Saudi Arabia. Previous research conducted on Muslim women's SRH focused exclusively on married women, partly because researchers may feel that it is inappropriate to ask unmarried women about sexual and reproductive matters (Alomair et al 2020a(Alomair et al , 2020b.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The majority of Islamic countries do not have formal sexual and reproductive health (SRH) education in schools, and many Muslim women have little to no access to SRH information (DeJong et al 2005). Muslim women have poor knowledge about basic reproductive functions, contraception and sexually transmitted infections (STIs) (Alomair et al 2020a(Alomair et al , 2020b. Lack of SRH knowledge has been linked to negative sexual and reproductive experiences and poor health outcomes (Rahman 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, another literature review based in 13 countries showed that Muslim women generally had poor knowledge about STIs signs and symptoms, prevention, diagnosis, and management. The review also revealed misconceptions that fueled blame and judgmental attitudes towards women who were infected [ 9 ].…”
Section: Introductionmentioning
confidence: 99%